Visual C++ .NET - H.M. Deitel
Written for programmers with a background in C, C++ or other high-level languages who want to learn Visual C++ .NET through the intermediate level this book appliesthe DEITEL signature LIVE-CODE approach to teaching programming and explores the MicrosoftVisual C++ .NET language in-depth. Key Visual C++ .NET concepts are presented in the context offully-tested programs, complete with syntax shading, detailed line-by-line descriptions and programoutputs. The book features 228 LIVE-CODE programs that contain 34,131 lines of proven VisualC++ .NET program code. In addition, the book includes 387 tips that help programmers build applicationsthat are portable, reusable and optimized for performance